2021
DOI: 10.1094/pdis-04-20-0816-re
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an Emerging Root-Knot Nematode Meloidogyne enterolobii in North Carolina, USA

Abstract: An emerging threat to agriculture, Meloidogyne enterolobii Yang & Eisenback, 1983 is a tropical species and considered to be the most damaging root-knot nematode (RKN) in the world because of its wide host range, aggressiveness, and ability to overcome resistance to RKN in many crops. It was first detected in the USA on ornamental plants in Florida in 2001, but has since been identified in North Carolina, South Carolina and Louisiana. Several thousand RKN populations were collected from North Carolina fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…On the other hand, the phylogenetic analysis of two M. enterolobii from rain tree and chilli compared to several studies indicates that it has a low level of nucleotide variation, indicating a lack of genetic diversity among M. enterolobii populations that results in having the sequences distinctly different from those of all other known RKN species (Onkendi & Moleleki, 2013; Shao et al, 2020; Ye et al, 2019). Similar results were reported by Ye et al (2021), who found a low nucleotide substitution site in M. enterolobii based on the quality of Sanger DNA sequencing. As such, there should be an extensive analysis to obtain a contig file based on multiple forward and reverse sequences and an evaluation of nucleotide position peaks and protein translation peaks.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the phylogenetic analysis of two M. enterolobii from rain tree and chilli compared to several studies indicates that it has a low level of nucleotide variation, indicating a lack of genetic diversity among M. enterolobii populations that results in having the sequences distinctly different from those of all other known RKN species (Onkendi & Moleleki, 2013; Shao et al, 2020; Ye et al, 2019). Similar results were reported by Ye et al (2021), who found a low nucleotide substitution site in M. enterolobii based on the quality of Sanger DNA sequencing. As such, there should be an extensive analysis to obtain a contig file based on multiple forward and reverse sequences and an evaluation of nucleotide position peaks and protein translation peaks.…”
Section: Discussionsupporting
confidence: 90%
“…TA B L E 3Both genes are highly conserved in M. incognita and the closely related to RKN, as demonstrated by blast search(Ye et al, 2019), which can detect multiple homologous species from the similarity in sequence and species complexes based on phylogenetic trees.Multiple analyses suggest a polyphyletic clade of M. incognita with similar sequence traits known as homoplasy, which explained by convergent evolution.that it has a low level of nucleotide variation, indicating a lack of genetic diversity among M. enterolobii populations that results in having the sequences distinctly different from those of all other known RKN species(Onkendi & Moleleki, 2013;Shao et al, 2020;Ye et al, 2019). Similar results were reported byYe et al (2021), who found a low nucleotide substitution site in M. enterolobii…”
supporting
confidence: 78%
See 1 more Smart Citation
“…As seen with many other agricultural crops, M. enterolobii management in tobacco is challenging. A very wide host range and ability to overcome resistance effective for other common species of root-knot nematodes make M. enterolobii unmanageable with currently available nematode management practices ( Brito et al ., 2007 ; Kiewnick et al ., 2009 ; Rutter et al ., 2019 ; Ye et al ., 2021 ; Khanal and Harshman, 2022 ). The use of fumigant nematicides is the most common method of nematode management in commercial agricultural production systems; however, none of the currently available fumigants are able to provide satisfactory management of M. enterolobii .…”
mentioning
confidence: 99%
“…However, drought tolerance has been identified in soybean curated in the United States Department of Agriculture (USDA) germplasm collection (Kunert & Vorster, 2020; Sloane et al., 1990). As another example, the guava root knot nematode ( Meloidogyne enterolobii ) has emerged as a pest in soybean, but no resistance has been detected in US cultivars (Wilson, 2018; Ye et al., 2021). Additionally, the seed protein content of many high‐yielding US commercial soybean cultivars released prior to 2017 is 38%–42% protein (dry weight) and is inadequate to meet the demand for meal with >47.5% protein (de Borja Reis et al., 2020; Patil et al., 2017).…”
Section: Introductionmentioning
confidence: 99%